Supplier Relationship Management - Jain, Deepak (Indian Journal of Computer Science, 2023)
Supplier management became important in the 1970s and 1980s for manufacturing companies. This was driven by globalization and an expanding supplier base. The focus was then on a structured onboarding process and performance management. There was not much system support. Today, Supplier Relationship Management (SRM) has become a strategic tool to achieve competitive advantage through collaborations and partnerships. This paper focuses on how SRM software can be used to achieve this. It covers the SRM process, architecture and features of SRM software.